2005
DOI: 10.1177/104063870501700519
|View full text |Cite
|
Sign up to set email alerts
|

Erysipelothrix Rhusiopathiae Septicemia in a Laughing Kookaburra (Dacelo Novaeguineae)

Abstract: Erysipelothrix rhusiopathiae (E. rhusiopathiae) septicemia was demonstrated in a captive Laughing kookaburra ( Dacelo novaeguineae). The bird died after a 2-week period of weakness and weight loss. At necropsy, the bird was emaciated and had reddened and wet lungs. Microscopic lesions were limited to hepatic and pulmonary congestion with focal thrombosis. Erysipelothrix rhusiopathiae was isolated by routine bacterial culture from several organs. Further characterization of the isolate by pulsed-field gel elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Thrombosis, hemorrhage, necrosis, and inflammation observed in several tissues in the lorikeet with previous reports in several bird species, although the extensive splenic and proventricular damage described in such reports was not noted in this case. 13,20,22,31 E. rhusiopathiae experimentally infected chickens showed similar pathological findings to those of the lorikeet in this study, including congestion, organomegaly (liver, spleen, and kidney), and vascular damage in several organs (intravascular fibrin thrombi), highly suggestive of disseminated intravascular coagulation and shock. 28 Routes of transmission for E. rhusiopathiae are believed to include direct horizontal transmission by asymptomatic carriers such as pigs, turkeys, or contaminated fish food, as well as indirect horizontal transmission by the means of fomites such as contaminated soil or mechanical vectors such as arthropods.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Thrombosis, hemorrhage, necrosis, and inflammation observed in several tissues in the lorikeet with previous reports in several bird species, although the extensive splenic and proventricular damage described in such reports was not noted in this case. 13,20,22,31 E. rhusiopathiae experimentally infected chickens showed similar pathological findings to those of the lorikeet in this study, including congestion, organomegaly (liver, spleen, and kidney), and vascular damage in several organs (intravascular fibrin thrombi), highly suggestive of disseminated intravascular coagulation and shock. 28 Routes of transmission for E. rhusiopathiae are believed to include direct horizontal transmission by asymptomatic carriers such as pigs, turkeys, or contaminated fish food, as well as indirect horizontal transmission by the means of fomites such as contaminated soil or mechanical vectors such as arthropods.…”
supporting
confidence: 78%
“…6,20 Genotyping homologous studies between strains coming from different outbreaks support the crossinfectivity between species. 22,23 The source of infection in the parrots in this report remains undetermined.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Although Erysipelothrix infection in the wild birds is sporadic, some massive outbreaks have been reported in Eared Grebes of the Great Salt Lake (Jensen and Cotter, 1976). Free ranging wild and captive birds such as racing pigeons (Cousquer, 2005), quails (Mutalib et al, 1995), emus (Swan and Lindsey, 1998;Morgan et al, 2011), pheasants (Milne et al, 1997;Hennig et al, 2006), chukar partridge (Pettit et al, 1976), malleefowl (Blyde and Woods, 1999), parrots (Livingston et al, 2013), chukars (Butcher and Panigrahy, 1985), Hawaiian crow (Work et al, 1999), blue penguin (Boerner et al, 2004), endangered kakapo (Gartrell et al, 2005), laughing kookaburra (Opriessnig et al, 2005), takahe, kiwi, and black stilts (Alley and Gartrell, 2019) showed infections with E. rhusiopathiae.…”
Section: Figure 1 Different Virulence Factors Of Erysipelothrix Rhusi...mentioning
confidence: 99%
“…Although mortality rate of erysipelas is generally low, but it can reach up to 25-50% (Stokholm et al, 2010). Mortality may range from less than 1% to more than 50% according to the organism's virulence, the host's susceptibility and immune response, and the presence of other complicating factors (Brickford et al, 1978;Opriessnig et al, 2005). Schmitt et al (2014) diagnosed erysipelas cases in a free-range laying flock with a high mortality of up to 7% per day.…”
Section: Clinical Signs and Pathologymentioning
confidence: 99%